A large‐scale assessment of plant dispersal mode and seed traits across human‐modified Amazonian forests. (17th February 2020) - Hawes, Joseph E.; Vieira, Ima C. G.; Magnago, Luiz F. S.; Berenguer, Erika; Ferreira, Joice; Aragão, Luiz E. O. C.; Cardoso, Amanda; Lees, Alexander C.; Lennox, Gareth D.; Tobias, Joseph A.; Waldron, Anthony; Barlow, Jos
Abstract: Quantifying the impact of habitat disturbance on ecosystem function is critical to understanding and predicting the future of tropical forests. Many studies have examined post‐disturbance changes in animal traits related to mutualistic interactions with plants, but the effect of disturbance on plant traits in diverse forests has received much less attention. Focusing on two study regions in the eastern Brazilian Amazon, we used a trait‐based approach to examine how seed dispersal functionality within tropical plant communities changes across a landscape‐scale gradient of human modification, including both regenerating secondary forests and primary forests disturbed by burning and selective logging. Surveys of 230 forest plots recorded 26, 533 live stems from 846 tree species. Using herbarium material and literature, we compiled trait information for each tree species, focusing on dispersal mode and seed size. Disturbance reduced tree diversity and increased the proportion of lower wood density and small‐seeded tree species in study plots. Disturbance also increased the proportion of stems with seeds that are ingested by animals and reduced those dispersed by other mechanisms (e.g. wind). Older secondary forests had functionally similar plant communities to the most heavily disturbed primary forests. Mean seed size and wood density per plot were positively correlated for plant species with seeds ingested by animals. Synthesis . Anthropogenic disturbance has major effects on the seed traits of tree communities, with implications for mutualistic interactions with animals. The important role of animal‐mediated seed dispersal in disturbed and recovering forests highlights the need to avoid defaunation or promote faunal recovery. The changes in mean seed width suggest larger vertebrates hold especially important functional roles in these human‐modified forests. Monitoring fruit and seed traits can provide a valuable indicator of ecosystem condition, emphasizing the importance of developing a comprehensive plant traits database for the Amazon and other biomes. Abstract : Anthropogenic disturbance has major effects on the seed traits of tree communities, with implications for mutualistic interactions with animals. The important role of animal‐mediated seed dispersal in disturbed and recovering forests highlights the need to avoid defaunation or promote faunal recovery. The changes in mean seed width suggest larger vertebrates hold especially important functional roles in these human‐modified forests. Monitoring fruit and seed traits can provide a valuable indicator of ecosystem condition, emphasizing the importance of developing a comprehensive plant traits database for the Amazon and other biomes. Sumário: Para melhor entender e prever o futuro das florestas tropicais é crítico quantificar o impacto de distúrbios antrópicos sobre as funções ecossistêmicas. Muitos estudos já avaliaram, após eventos de distúrbios, mudanças nas características funcionais da fauna relacionadas com interações mutualísticas com a flora. Porém, o efeito de distúrbios antrópicos nas características funcionais da comunidade arbórea de florestas megadiversas é ainda pouco estudado. Este estudo focou em duas regiões distintas da Amazônia oriental brasileira, e utilizou um método baseado em características funcionais para entender como a dispersão de sementes, dentro de comunidades arbóreas, pode ser modificada ao longo de um gradiente de distúrbio antrópico, incluindo florestas secundárias e florestas primárias afetadas por fogo e corte seletivo. Foram conduzidos inventários florestais em 230 parcelas de estudo, amostrando um total de 26.533 indivíduos vivos pertencentes a 846 espécies arbóreas. A partir de material depositado em herbários e informações da literatura, as características funcionais, para cada espécie arbórea, foram compiladas, focando no tipo de dispersão e no tamanho da semente. Os distúrbios antrópicos reduziram a diversidade arbórea e aumentaram a proporção tanto de espécies com baixa densidade de madeira, como de espécies com sementes pequenas. Os distúrbios antrópicos também aumentaram a proporção de árvores com sementes que são ingeridas por animais e diminuíram àquelas dispersas por outros mecanismos, como o vento. Florestas secundárias em estágios mais avançados de sucessão apresentaram comunidades arbóreas funcionalmente semelhantes àquelas de florestas primárias com maior grau de distúrbios antrópicos. A nível de parcela, o tamanho médio das sementes e a densidade da madeira foram positivamente correlacionados para plantas com sementes dispersas por animais. Síntese : Os distúrbios antrópicos influenciaram amplamente as características funcionais de sementes das comunidades arbóreas, com implicações diretas para as relações mutualísticas com a fauna. A elevada importância de animais na dispersão de sementes tanto em florestas primárias que sofreram distúrbios antrópicos assim como em florestas secundárias ressalta a importância de se evitar a defaunação e de promover a recuperação da fauna. As mudanças no tamanho médio da largura da semente sugerem que grandes vertebrados tem um papel funcional especialmente importante em florestas antropizadas. O monitoramento de características funcionais de frutos e sementes pode prover um valioso indicador das condições de ecossistemas, enfatizando a importância da criação de uma base de dados compreensiva para a Amazônia e para outros biomas contendo características funcionais da vegetação.